Policy effects of China’s water rights trading on grain production: the role of market incentives in promoting sustainability - Yin, Ning; Luo, Sichang; Xia, Yulian (Frontiers in Sustainable Food Systems, 2025)
IntroductionSince water is an essential input in agricultural production, the reform of water rights system can pose significant influence on water resource allocation and utilization within agri-food systems. Water rights trading has been recognized as an innovative market incentive strategy to promote sustainable water use. This study investigates the role of China’s water rights trading policy played in promoting the green water use efficiency of grain production.MethodsA three-stage DEA method is adopted to evaluate the green water use efficiency with a provincial panel data from 2006 to 2020. A PSM-DID model, based on the quasi-natural experiment of China’s water rights trading pilots in 2014, is employed to analyze policy effects and to explore the role of market mechanism.ResultsResults have shown that the green water use efficiency of grain production has been significantly improved after the implementation of China’s water rights trading policy, and technological innovation is found to exert a mediating effect. The policy effect appears more pronounced and robust in national water rights trading pilots than in provincial ones. Heterogeneity is also detected from the perspective of water resource endowment. The efficiency improvement effect is more pronounced in areas with higher per capita water endowment or in China’s main grain-selling areas.DiscussionThe findings reveal benefits of utilizing market mechanisms to improve the water use efficiency considering environmental constraints. This study gives reference for regions aiming to implement resource conservation and environmentally friendly policies, and also provides inspiration for fostering the sustainable development of grain production in developing countries facing resource scarcity.